DAMPAK PENGGUNAAN INPUT PRODUKSI TERHADAP EFISIENSI TEKNIS USAHATANI JAGUNG PROGRAM UPAYA KHUSUS (UPSUS) DI KABUPATEN MUARO JAMBI - INDONESIA - Riri Oktari Ulma; Saidin Nainggolan (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2020)
This research aims to analyze the allocation of using production inputs, production, and technical efficiency of maize for UPSUS and non-UPSUS programme of corn farming. This study held in two sample villages, namely: Mekar Sari village and Sogo village which were determined purposively. The sample size was 47 farmers participating in the UPSUS program and 36 non-UPSUS farmers. Simple Random Sampling method is applied in this study. The data collection method used the survey with questionnaire. Cobb Douglas production function method and Chow Test are applied to analyze the data. The measurement of technical efficiency is used the Productivity Function Model. The results showed that the maize UPSUS program was able to significantly increase the allocation of the use of production inputs, productivity and technical efficiency. This means that the UPSUS program can be efficient and successful in achieving its production target of 5 ton/ha and additional production of 0.8 ton/ha.